1991
DOI: 10.1557/proc-246-115
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Twinning, Slip, Martensite Formation and Crack Inhibition in the B2-Type Zr50Pd35Ru15 Alloy

Abstract: Enhanced room temperature toughness of the Zr50Pd35Ru15B2 phase alloy was found to be a result of the activation of an additional deformation mode besides the b=[001] dislocation slip mode - {114}-type mechanical twinning. The twinning is a true one, i.e. there is no change in the ordered crystal structure. Another additional mode of plastic deformation, expected for more Pd rich alloys, is the formation of stress-induced martensite. The martensite was found to have a CrBtype structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Alternative In addition to theto dislocation slip occurring during modes of plastic deformation, there could can also be mechanical twinning and stress-induced martensitic phase transformation [22]. Twinning can re-orient portions of a grain to facilitate further dislocation motion, thereby compensating for inadequate numbers of independent slip systems [17,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative In addition to theto dislocation slip occurring during modes of plastic deformation, there could can also be mechanical twinning and stress-induced martensitic phase transformation [22]. Twinning can re-orient portions of a grain to facilitate further dislocation motion, thereby compensating for inadequate numbers of independent slip systems [17,23].…”
Section: Discussionmentioning
confidence: 99%
“…TEM investigation indicated that the CrB-type B33 Mechanical twinning of {114}-type observed in B2 structure, <100>-type slip, and martensitic phase transformation were found to be responsible for the enhanced room temperature ductility of 6.6% elongation in the B2 structured Zr50Pd35Ru15 alloy [22,25]. In Zr50Co39Ni11 alloy the lenticular B33 martensites having lattice parameters The previous worksPrevious research has have shown that the dominate dominant slip systems in RM intermetallic compounds are {110}<001> and {100}<001>.…”
Section: Discussionmentioning
confidence: 99%
“…So far the mechanism of B2→B27 phase transformation is not solved. A model similar to that published in [16] will be presented in a separate paper. In the present study the impurity phases such as Y 2 O 3 and YCu 2 were not observed in YCu specimens.…”
Section: Methodsmentioning
confidence: 99%
“…Twinning can re-orient portions of a grain to facilitate further dislocation motion, thereby compensating inadequate numbers of independent slip systems. Plastic deformation due to a martensitic phase transformation or redistribution of martensite variants has been observed in many shape memory alloys [16,17]. Ibarra et al [18] showed that YCu undergoes a B2 (CsCl-type) to B27 (FeB-type) martensitic phase transformation at about 140 K by neutron diffraction measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The compound ZrPd is the second long period analog of TiNi and is the basis of alloys having exceptional resistance to sliding wear. [2] The compound HfPt is the third long period analog of TiNi but its properties are not well known, due partly to the absence of a phase diagram for the Hf-Pt alloy system. The Hf-Pt system has become the last binary alloy system belonging to this class for which no phase diagram currently exists.…”
Section: Introductionmentioning
confidence: 99%